Efektivitas Penggunaan Model Guided Discovery Learning Terhadap Hasil Belajar Siswa Pada Materi Laju Reaksi Di Kelas XI - Karlina, Vina; Asma, Rita (Integrated Science Education Journal, 2022)
Research Objectives: This study aims to determine the effectiveness of the implementation of the Guided Discovery Learning learning model on the reaction rate material. Methodology: The research method used is a mix method research method that combines quantitative research and qualitative research. The design used is a quasi-experimental research design with a time-series design without a control class. There is one class that is used as a sample, namely class XI MIPA 6. The sampling technique used is purposive sampling. The research instrument used was an observation sheet on teacher and student activities in carrying out the model and student learning outcomes tests in the form of essays. Main findings: Based on the results of data analysis, it was found that the effectiveness of using the Guided Discovery Learning Model in terms of student learning outcomes at the first meeting increased compared to the pretest (25.66%, 73.88%), and at the second meeting (73.88%, 74 ,33%). The data is supported by quantitative observation data which shows a good category (76%), and qualitative observation data of the learning process has been carried out well. However, at the third meeting, learning outcomes decreased drastically by around 53.16%. This is relevant to the qualitative data which also shows that the learning process was not carried out well at the third meeting. Research novelty: The novelty of this research is the use of the Guided Discovery Learning model to see student learning outcomes.